Oral cancer and the role of the Dentist in early diagnosis: An integrative review (Research, Society and Development, 2023)
Oral cancer ranks among the top ten types of cancer with the highest mortality rates worldwide. Early diagnosis promotes a greater chance of patient survival, and the dentist must be the qualified professional to carry out this procedure. This study is an integrative literature review with the aim of evaluating publications related to the role of dentists in the early diagnosis of oral cancer in primary care. The Biblioteca Virtual da Saúde (BVS) and SciELO databases had been used with the descriptors “cancer” “dentistry” “primary” and “cancer” “dentistry”, respectively, considering the last five years (2019-2023). After selection, 15 studies were analyzed focusing on the dentist's role in diagnosing oral cancer in primary care. The results demonstrate weaknesses in the primary oral care system for early diagnosis of oral cancer. Thus, this study reinforces the need for continuous education of oral primary care professionals, as well as public investments in primary oral health care to the early diagnosis of oral cancer.